Redefining the H-NS protein family: a diversity of specialized core and accessory forms exhibit hierarchical transcriptional network integration. Issue 18 (7th September 2020) - Fitzgerald, Stephen; Kary, Stefani C; Alshabib, Ebtihal Y; MacKenzie, Keith D; Stoebel, Daniel M; Chao, Tzu-Chiao; Cameron, Andrew D S
Abstract: H-NS is a nucleoid structuring protein and global repressor of virulence and horizontally-acquired genes in bacteria. H-NS can interact with itself or with homologous proteins, but protein family diversity and regulatory network overlap remain poorly defined. Here, we present a comprehensive phylogenetic analysis that revealed deep-branching clades, dispelling the presumption that H-NS is the progenitor of varied molecular backups. Each clade is composed exclusively of either chromosome-encoded or plasmid-encoded proteins. On chromosomes, stpA and newly discovered hlpP are core genes in specific genera, whereas hfp and newly discovered hlpC are sporadically distributed. Six clades of H -NS p lasmid p roteins (Hpp) exhibit ancient and dedicated associations with plasmids, including three clades with fidelity for plasmid incompatibility groups H, F or X. A proliferation of H-NS homologs in Erwiniaceae includes the first observation of potentially co-dependent H-NS forms. Conversely, the observed diversification of oligomerization domains may facilitate stable co-existence of divergent homologs in a genome. Transcriptomic and proteomic analysis in Salmonella revealed regulatory crosstalk and hierarchical control of H-NS homologs. We also discovered that H-NS is both a repressor and activator of Salmonella Pathogenicity Island 1 gene expression, and both regulatory modes are restored by Sfh (HppH) in the absence of H-NS.